Famílias de crianças com deficiência: a vivência do diagnóstico ao processo de reabilitação. - Melo, Etelvina Sampaio (2019)
A person with a disability is one who has a long-term disability of a physical, mental, intellectual or sensorial nature. In order to care for children with disabilities, it is necessary to increase the interaction between health professionals and their families, through the analysis of the experiences of families living with children with disabilities, provide health professionals with subsidies for qualification and planning of care, guidance and assistance to these families and their caregivers to enhance care, as well as the visibility achieved in the elaboration of public policies. For this, it is necessary to know the objective and subjective conditions that permeate their lives. In this perspective, this study aims to analyze the experiences of families living with children with disabilities. This is a descriptive research with a qualitative case study approach, conducted with families of children with disabilities accompanied by the Rehabilitation Center in Sobral-CE during the months of August to September 2018. Data collection was done through a semi-structured interview with 21 family members and data analysis was recorded by cross-synthesis of the data. All ethical aspects of the research were respected and considered in accordance with CNS Resolution 466/2012. The experiences were presented through the profile of families and children in view of the need to know the socioeconomic conditions, which have important repercussions on the daily care of these, and also the analysis of the participants' testimonies that portray the experience of living with which were organized in the following thematic categories: search for knowledge for the management of the child; process of family acceptance; difficulties in family life, subdivided into: difficulty in relation to child dependence and family support, difficulty in socialization, difficulty in communicating with the child, difficulty with the lack of preparation of the school and difficulty with prejudice; and process of rehabilitation and development of the child. Deficiency in the child can bring insecurity and feeling of incapacity to the family. Many difficulties were evidenced by the changes that occur in the daily life of the family, especially in the reality of the primary caregiver who is immersed in the daily life of the child with a disability and shows that she suffers from work overload and lack of social and family support as well as prejudice of society and the lack of school support. Despite this, some participants showed that it is possible to adapt and experience certain situations with management, favoring the child's development and their relationship with society. They affirm that the search for information and knowledge about disability was important for the process of acceptance and adaptation. Thus, it is imperative that health professionals know the deficiencies, the ways of handling and treatment and are able to pass information clearly to the family. Further studies on the families of children with disabilities are suggested, in order to investigate and understand the difficulties, the creation of multidisciplinary family accompaniment programs, coexistence groups and the improvement of qualification programs for health professionals and education.